Association Between Sensorineural Hearing Loss and Various Stages of Chronic Kidney Disease - Kotian, Shashank; Naik, Ashok S.; Revanasiddappa, Manjunath; Goutham, Maniyankode Krishnamohan (Journal of Health and Allied Sciences NU, 2021)
Objectives To compare the proportion of sensorineural hearing impairment (SHI) among patients of chronic kidney disease (CKD) stages 3&4 with CKD stage 5.Materials and Methods This is a cross-sectional study of 30 patients with CKD stages 3 and 4 and 30 patients in stage 5. All patients had an audiological evaluation with pure tone audiometry.Results Our study had 49 males (82%) and 11 females (18%), with the age ranging from 20 to 60 years (mean: 45.13 years). The mean SHI values in stage 3&4 were 28.44 dB and in CKD stage 5 was 31.22 dB. In the right ear, the mean hearing loss in stage 3, stage 4, and stage 5 was 28.17 dB, 28.67 dB, and 31.84 dB, respectively. In the left ear, the mean SHI values in stage 3, stage 4, and stage 5 were 27.05 dB, 31.89 dB, and 30.61 dB, respectively.The mean SHI in stage 3&4 for age group 20 to 30 years was 13.66 dB, for 31 to 40 years was 26.33 dB, for 41 to 50 years was 35.18 dB, for 51 to 60 years was 37.12 dB. The mean SHI in stage 5 for the age group of 20 to 30 years was 16.48 dB, for 31 to 40 years was 28.29 dB, for 41 to 50 years was 31.82 dB, for 51 to 60 years was 34.35 dB. There was a significant correlation between hearing loss and CKD with respect to age (p < 0.001). The duration of renal illness and associated comorbidities was not a significant contributor to hearing loss in our study (p > 0.05).Conclusion As per our study, with progression in the stage of chronic kidney disease, the hearing loss also increased indicating a possible link between the two. We also noted that the hearing loss increased with the increasing age.
Keywords: chronic kidney disease; pure tone audiometry; sensorineural hearing impairment